2016
DOI: 10.1002/humu.22938
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Whole Gene Deletions and Large Rearrangements to the Mutation Spectrum in Inherited Tumor Predisposing Syndromes

Abstract: ABSTRACT:Heterozygous whole gene deletions (WGDs), and intragenic microdeletions, account for a significant proportion of mutations underlying cancer predisposition syndromes. We analyzed the frequency and genotype-phenotype correlations of microdeletions in 12 genes (BRCA1, BRCA2, TP53, MSH2, MLH1, MSH6, PMS2, NF1, NF2, APC, PTCH1, and VHL) representing seven tumor predisposition syndromes in 5,897 individuals (2,611 families) from our center. Overall, microdeletions accounted for 14% of identified mutations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 63 publications
4
53
0
Order By: Relevance
“…1b). Our data support evidence on a significant contribution from whole-exon deletions in MSH2 and PMS2, and demonstrate a higher rate of large deletions than previously reported in MLH1 (28,29). Of the 201 sequence variants reported, 137 are available in the InSiGhT database, whereas 64 have not previously been reported.…”
Section: Discussionsupporting
confidence: 90%
“…1b). Our data support evidence on a significant contribution from whole-exon deletions in MSH2 and PMS2, and demonstrate a higher rate of large deletions than previously reported in MLH1 (28,29). Of the 201 sequence variants reported, 137 are available in the InSiGhT database, whereas 64 have not previously been reported.…”
Section: Discussionsupporting
confidence: 90%
“…Deletions of CPGs with substantial childhood-onset risks such as SMARCB1 (malignant rhabdoid tumour) and TP53 (brain and sarcoma) also appear to be not infrequent and there is no evidence these deletions are less penetrant than point mutations 27. On the other hand, we also detected an inherited deletion encompassing BMPR1A (P005), where there was no family history of polyposis.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, recent analysis of a range of CPGs showed that large deletions including whole gene deletions were associated with fairly typical cancer predisposition compared with point mutations 27. Deletions of CPGs with substantial childhood-onset risks such as SMARCB1 (malignant rhabdoid tumour) and TP53 (brain and sarcoma) also appear to be not infrequent and there is no evidence these deletions are less penetrant than point mutations 27.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions and duplications of whole exons, termed ‘exon copy number variants’ or ‘exon CNVs’, are an important class of clinically relevant gene mutations 4 . Accurate exon CNV detection has proved difficult in targeted NGS data, particularly if only a single exon is affected 5 .…”
Section: Introductionmentioning
confidence: 99%